Acromegaly as a Multisystem Disease – Analysis of Metabolic Complications. Review of Current Literature - Krzyżanowska, Daria Anna; Bętkowska, Paula; Strzelczyk, Magdalena; Wziątek , Joanna; Koziołek, Iwona; Pabis, Gabriela; Fatyga, Patrycja; Fatyga, Wiktoria; Kowalik, Piotr; Dowierciał, Kinga (Quality in Sport, 2025)
Introduction and purpose Acromegaly is an endocrine disorder resulting from an excess of growth hormone (GH), most often caused by a pituitary adenoma. In addition to typical somatic symptoms, a key clinical aspect is its complications (particularly metabolic). Chronic exposure to GH and insulin - like growth factor (IGF-1) significantly affects lipid and carbohydrate metabolism. This paper presents the current state of knowledge on acromegaly, including the most common metabolic disorders occurring during its course. The aim of this review is to deepen the understanding of acromegaly as a systemic disease, with particular emphasis on its metabolic complications. Material and methods The paper analyzes scientific publications on acromegaly and its metabolic complications published between 2008 and 2024. To gather relevant data, the literature available on PubMed was used, utilizing the following keywords: acromegaly, metabolic disorders, complications. Results The analysis of available scientific publications revealed the presence of metabolic disorders in the majority of patients with acromegaly. Lipid disturbances affect as many as 74% of patients. These individuals typically exhibit hypercholesterolemia, hypertriglyceridemia, and decreased HDL-C levels. Equally significant are disturbances in glucose metabolism, affecting more than 50% of patients. The data confirm that prolonged excess of GH and IGF-1 significantly disrupts the body’s homeostasis, requiring monitoring and comprehensive treatment. Conclusions Acromegaly is a potentially fatal disease whose effects extend far beyond the endocrine system. Its complications significantly increase cardiovascular risk, worsen patient prognosis, and negatively impact their quality of life (QoL). To improve treatment outcomes, a holistic approach to patient care, appropriate metabolic monitoring, and individualized treatment are essential.